2013
DOI: 10.1155/2013/524701
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and Characterization of New Palladium(II) Thiosemicarbazone Complexes and Their Cytotoxic Activity against Various Human Tumor Cell Lines

Abstract: The palladium(II) bis-chelate complexes of the type [Pd(TSC1-5)2] (6–10), with their corresponding ligands 4-phenyl-1-(acetone)-thiosemicarbazone, HTSC1 (1), 4-phenyl-1-(2′-chloro-benzaldehyde)-thiosemicarbazone, HTSC2 (2), 4-phenyl-1-(3′-hydroxy-benzaldehyde)-thiosemicarbazone, HTSC3 (3), 4-phenyl-1-(2′-naphthaldehyde)-thiosemicarbazone, HTSC4 (4), and 4-phenyl-1-(1′-nitro-2′-naphthaldehyde)-thiosemicarbazone, HTSC5 (5), were synthesized and characterized by elemental analysis and spectroscopic techniques (IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
3
22
0
3
Order By: Relevance
“…In the 13 C NMR spectra of synthesized compounds, Figure 3, carbon atoms due to keto C=O and azomethine C=N groups display resonance signals at 165.5 and 147.4 ppm in Empp-Ph and Prmpp-Ph, respectively [24]. Also the signals due to aromatic carbon are observed as multiplets and resonate in the chemical shift range of 147.4 and 112.9 ppm.…”
Section: 2mentioning
confidence: 97%
“…In the 13 C NMR spectra of synthesized compounds, Figure 3, carbon atoms due to keto C=O and azomethine C=N groups display resonance signals at 165.5 and 147.4 ppm in Empp-Ph and Prmpp-Ph, respectively [24]. Also the signals due to aromatic carbon are observed as multiplets and resonate in the chemical shift range of 147.4 and 112.9 ppm.…”
Section: 2mentioning
confidence: 97%
“…When designing new antitumor agents, the similarity in the chemistry of the Pt II and Pd II compounds has led to the study of palladium antitumor drugs with high activity. [22][23][24][25][26] Some of them are stabilized by chelates, as Schiff bases, or by voluminous ligands with monodentate nitrogen atoms, [22] which presented activity in HeLa cell line. It has been reported that trans-Pd compounds with Schiff base ligands have better activity than the cis-Pd compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Las tiosemicarbazonas son una clase importante de ligandos con átomos donadores de electrones, como el azufre y el nitrógeno, que actúan como agentes quelantes de metales de transición (10) y exhiben actividad antineoplásica (5,11,12). De hecho, las tiosemicarbazonas y sus complejos metálicos son de gran interés por su amplio rango de efectos biológicos (13,14), ya que tanto los ligandos derivados de ellas como los complejos metálicos de transición tienen otras propiedades farmacológicas antivirales, antibacterianas, antifún-gicas, antiparasitarias y antitumorales (3,10,(15)(16)(17)(18).…”
unclassified
“…De hecho, las tiosemicarbazonas y sus complejos metálicos son de gran interés por su amplio rango de efectos biológicos (13,14), ya que tanto los ligandos derivados de ellas como los complejos metálicos de transición tienen otras propiedades farmacológicas antivirales, antibacterianas, antifún-gicas, antiparasitarias y antitumorales (3,10,(15)(16)(17)(18).…”
unclassified
See 1 more Smart Citation